Phraseologismen im Bereich der Sexualität : eine lexikographische Analyse an deutschen und polnischen Beispielen - Lidzba, Aleksandra; Suchorab, Krystian (. Studia Germanistica. - Ostrava : Ostravská univerzita v Ostravě, [2009]-. - Online-Ressource. - ISSN 2571-0273 28, 2021)
People's sex life is very often, if not always, taboo in everyday life. The theming of this area of life is made possible by various linguistic means that allow one to speak about this content. Phraseological units also serve this purpose. The starting point of this article is the definition of phrasemes according to Burger (2015:11): "Firstly, they [phraseologisms] consist of more than one word; secondly, the words are not put together for this one occasion, but are combinations of words that we, as German speakers, know exactly in this combination (possibly with variants), similar to how we know German words as individual items". In addition, it is noteworthy that thanks to the characteristic of idiomaticity (cf. Fleischer 1982:30), this taboo is particularly reinforced. At the center of our analysis are phrasemes related to sex life. The research material was taken from German and Polish dictionaries. The purpose of the presentation is to create a typology of thematic areas which are characterized with the help of phrasemes relating to sex life in German and Polish. The article is based on the following definition of a taboo: "an unwritten law that forbids doing certain things based on certain beliefs within a society" (Duden 2015:1735).